Analisis Majāz Mursal dalam Surah Al-Mursalat: Perspektif Linguistik dan Tafsir - Niken Salindri (Ta'bir Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Ilmu Kebahasaaraban, 2025)
This study aims to analyze and identify the use of majāz mursal in Surah Al-Mursalat and relate it to the concepts of linguistics and Qur'anic interpretation. Using descriptive qualitative research method, this study maps the various forms of majāz mursal found in the surah, based on the semantic relationship between the lafaz and the concept conveyed. The main data sources in this study are classical and contemporary tafsir and balaghah literature that discuss majāz mursal. The results show that in Surah Al-Mursalat there are 21 verses that contain majāz mursal with a variety of 'alaqah, such as cause-effect, part-whole, situation, place, and temporal aspects. Majāz mursal in this surah plays a role in strengthening the rhetorical message and aesthetics of the Qur'anic language as well as providing a deeper dimension of meaning to the verses that contain eschatological aspects. A comparison between linguistic and exegetical approaches shows that the interpretation of majāz mursal in Surah Al-Mursalat not only clarifies the structure of the language but also provides new insights into the translation and interpretation of the Qur'ān more broadly. This research therefore contributes to the development of Qur'anic balaghah, tafsir, and linguistic studies, and opens up opportunities for further research to explore majāz mursal more accurately and carefully.